Comparative density of CCK- and PV-GABA cells within the cortex and hippocampus - Paul David Whissell; Janine Dominique Cajanding; Nicole eFogel; Jun Chul eKim; Jun Chul eKim (Frontiers Media S.A., 2015)
Cholecystokinin (CCK)- and parvalbumin (PV)-expressing neurons constitute the two major populations of perisomatic GABAergic neurons in the cortex and the hippocampus. As CCK- and PV-GABA neurons differ in an array of morphological, biochemical and electrophysiological features, it has been proposed that they form distinct inhibitory ensembles which differentially contribute to network oscillations and behaviour. However, the relationship and balance between CCK- and PV-GABA neurons in the inhibitory networks of the brain is currently unclear as the distribution of these cells has never been compared on a large scale. Here, we systemically investigated the distribution of CCK- and PV-GABA cells across a wide number of discrete forebrain regions using an intersectional genetic approach. Our analysis revealed several novel trends in the distribution of these cells. While PV-GABA cells were more abundant overall, CCK-GABA cells outnumbered PV-GABA cells in several subregions of the hippocampus, medial prefrontal cortex and ventrolateral temporal cortex. Interestingly, CCK-GABA cells were relatively more abundant in secondary/association areas of the cortex (V2, S2, M2, and AudD/AudV) than they were in corresponding primary areas (V1, S1, M1 and Aud1). The reverse trend was observed for PV-GABA cells. Our findings suggest that the balance between CCK- and PV-GABA cells in a given cortical region is related to the type of processing that area performs; inhibitory networks in the secondary cortex tend to favour the inclusion of CCK-GABA cells more than networks in the primary cortex. The intersectional genetic labelling approach employed in the current study expands upon the ability to study molecularly defined subsets of GABAergic neurons. This technique can be applied to the investigation of neuropathologies which involve disruptions to the GABAergic system, including schizophrenia, stress, maternal immune activation and autism.